An Analysis of the Development of Preschoolers' Natural Science Concepts from the Perspective of Framework Theory - Nikolaos Christodoulakis; Karina Adbo (MDPI AG, 2024)
The aim of the study was to explore children's learning of natural science, and the authors chose a literature review as the means to achieve this aim. As the research into children's emerging science is fragmented into many different theoretical perspectives and many kinds of studies are included, research results deriving from the field can be difficult to summarize. To resolve this issue, Vosniadou's framework theory was used as the tool for data analysis. Results show emergence as a dynamic interaction between intuitive and counter-intuitive concepts leading to synthetic and scientific models in combination with developing epistemological and ontological skills. The accumulation of synthetic concepts seems to be the most common result of early formal educational input. Both intuitive and synthetic models are predecessors for scientific concepts and models, and these models as such are very important for emerging science. The conclusions suggest that diverse science experiences should bring about more synthetic models. This subsequently creates a wider basis for further development. Another important factor of emergence is the development of children's epistemic skills and ontological shifts. Research results suggest that it is important for teachers to support children's epistemic and ontological skills. Enhancing children's understanding about causality and ontology is an important step towards developing formal concepts of science.